การศึกษาปัจจัยที่ส่งผลต่อสมบัติของยางแผ่นรมควันเกรดพรีเมียม - สายสุณี จิตกล้า (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Although the mechanical properties of ribbed smoke sheet (RSS) are superior to other types of dry rubber, the inconsistency in quality of rubber resulted in the continuous decline in the consumption of RSS in the tire industry. Currently, Rubber Authority of Thailand has set the production standard to control and obtain the RSS with high consistence in both physical and mechanical properties. The obtained RSS is called "RSS premium grade" or "RSS-P" to better understand the parameters that cause variation in the properties of RSS. This research studied the influence of production conditions, rubber tapping season and rubber planting area on both physical and mechanical properties of RSS. The results showed that when using latex with different dry rubber contents and different formic acid concentrations for coagulation, the properties of the RSS were not the same. It was found that when the dry rubber content and the concentration of formic acid increased, it resulted in an increase in volatile matter of the RSS. Because the rubber lump obtained from the coagulation of latex with acid was hard, making it difficult to roll into thin sheets. Therefore, the water in rubber did not completely evaporate. When increasing the amount of dry rubber, PO, PRI and Mooney viscosity increased. Changing the dry rubber content in latex from 20% (condition used in the production of RSS premium grade) to 18, 20 and 25% by weight resulted in differences in tensile strength. The maximum difference was 2.1 MPa. Increasing the formic acid concentration resulted in a decrease in Po, PRI and Mooney viscosity. Changing formic acid concentration from 4% (condition used in the production of RSS premium grade) to 2, 3, 5, 8 and 10% by volume resulted in the maximum difference in tensile strength of rubber at 3.2 MPa. When considering rubber tapping seasons, the latex obtained during the defoliation of the rubber tree had a lower dry rubber content and higher amounts of various elements. This led to the different values of ash and nitrogen in RSS. Mooney viscosity of RSS notably depends on the rubber tapping season. The RSS prepared from the latex obtained during normal tapping had higher Mooney viscosity than the one obtained from the closing tapping period. RSS obtained from the Northeastern region had higher ash content than that obtained from the South. The ash content was caused by the different substances and minerals in the soil. However, the rubber obtained from the two sites had no significant difference in Po, PRI and Mooney viscosity.